Intranet-baseret koncernfagleksikografi - Simonsen, Henrik Køhler (Nordiske Studier i Leksikografi, 2003)
The overall purpose of this contribution is to present a number of overall theoretical considerations on corporate LSP Intranet lexicography and some conceptual considerations on the design and development of an Intranet-based lexicographic knowledge management system in a corporation or organization. Such considerations are needed, as a conventional user approach is not enough and because a corporation or an organization makes heavy demands of the lexicographic artifact. Consequently, it is my thesis that focus on the individual user is not enough. The increased user approach and the potential of the medium used also necessitate new metalexicographic considerations on the conception and design of Intranet-based lexicographic knowledge management systems in a corporation or an organization, which integrate the enhanced potential inherent in the increased user approach as illustrated in TeleLex. TeleLex is a lexicographic knowledge management system and is the developmental result of a Danish Industrial Ph.D. Fellowship Programme, whose parties are the Aarhus School of Business (ASB), the Academy of Technical Sciences (AT V) and Tele Danmark Communications A/S (TDC), where TeleLex was developed and implemented.